A shock tube facility to generate blast loading on structures. Issue 3 (September 2016) - Aune, Vegard; Fagerholt, Egil; Langseth, Magnus; Børvik, Tore
This study evaluates the performance of a new shock tube facility used to produce blast loading in controlled laboratory environments. The facility was found to generate a planar shock wave over the tube cross section by measuring the pressure distribution on a massive steel plate located at the end of the tube. The properties of the shock wave proved to be a function of driver length and driver pressure, and the positive phase of the measured pressure–time histories was similar to those generated from actual far-field explosive detonations. However, the shock tube is also suited to investigate fluid–structure interaction effects and the behaviour of materials in blast events. This was demonstrated using a three-dimensional digital image correlation technique to measure the deformation field of thin steel plates. Synchronization of the three-dimensional digital image correlation and pressure measurements enabled a thorough investigation of the entire experiment and identification of fluid–structure interaction effects. Finally, one-dimensional numerical simulations were performed to investigate the wave patterns during the experiments.